Blue Methylene Retrieval using Silica-Salicylic Acid Modified Filtering - Desriana Chrisyanti; Gunawan Gunawan; Abdul Haris (Jurnal Kimia Sains dan Aplikasi, 2018)
The retrieval of methylene blue using a silica-modified sulfide-salicylic acid has been carried out. Salicylate-silica-acid alloys have been prepared by comparing the four media ie filter paper, silica-filter paper, salicylic acid-filter paper and salicylic acid-silica-filter paper. This study aims to study the recovery of methylene blue using salicylic acid-modified silica filtering with various parameters on the adsorption and desorption process. The results showed that the salicylic acid-silica alloy could improve the capability of methylene blue removal. The result of pH variation on the adsorption process showed that at pH 7 methylene blue can be taken 92.89%. Whereas at concentration variation, salicylic acid at 5 mM can take methylene blue equal to 92.86%. The desorption results showed that pH 1 methylene blue could be desorbed at 308.89 mg/g, while the variation of contact time of desorption ie at 110 minutes could an saturate the blue methylene by 589,61 mg/g. The UV-Vis analysis showed a decrease in absorbance in salicylic acid after contact with silica. The FTIR analysis also shows that in salicylate-silica-acid alloys there are Si-O groups derived from silica and C = O derived from salicylic acid.